Effect of Sales Volatility and Operating Cash Flow on Earnigs Persistence at PT. Nusantara II Plantation Tanjung Morawa - Indi Fadliah; Hasbiana Dalimunthe; Linda Lores; Desy Astrid Anindya (Enrichment : Journal of Management, 2022)
This study aims to determine the effect of sales volatility and operating cash flow on earnings persistence at PT. Nusantara II Tanjung Morawa Plantation. The type of research used is the associative method. The sample in this study is a monthly report from 2018 to 2021. The source of data used in this study is secondary data. The data collection technique is documentation with the data analysis technique used in this study is multiple linear regression analysis. The results showed that the sales volatility variable had a positive and significant effect on earnings persistence. operating cash flow variable has a positive and significant effect on earnings persistence. The variables of sales volatility and operating cash flow have a simultaneous effect on earnings persistence at PT. Nusantara II Tanjung Morawa Plantation.